2021
DOI: 10.3390/ijerph18126626
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle Factors and Sleep Health across the Lifespan

Abstract: Sleep health, operationalized as a multidimensional construct consisting of sleep regularity, satisfaction, alertness, timing, efficiency, and duration, is an emerging concept in the field of sleep medicine which warrants further investigation. The purpose of the present study was to: (1) compare sleep health across the lifespan, (2) determine lifestyle factors associated with sleep health, and (3) examine whether lifestyle factors associated with sleep health varied between and within age groups. Participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 41 publications
(72 reference statements)
0
9
0
Order By: Relevance
“…We found that not engaging in reading was associated with long sleep duration and not watching TV were associated with long sleep duration and poor sleep quality. Dzierzewski et al (51) and Xie et al (52) both found that excessive the duration of watching TV predicted poorer sleep status among older people. Our findings further provided that never watching TV was also harmful to sleep, not only excessive the duration of watching TV.…”
Section: Discussionmentioning
confidence: 99%
“…We found that not engaging in reading was associated with long sleep duration and not watching TV were associated with long sleep duration and poor sleep quality. Dzierzewski et al (51) and Xie et al (52) both found that excessive the duration of watching TV predicted poorer sleep status among older people. Our findings further provided that never watching TV was also harmful to sleep, not only excessive the duration of watching TV.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond examining specific elements of sleep disruption, a relatively new term can be used to obtain a global view of sleep—namely, sleep health. Sleep health integrates multiple elements of sleep, such as duration, timing, regularity, efficiency and satisfaction [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, female elderly report more sleep disturbance ( 11 ). Malnutrition, lack of exercise, long-time TV watching, and illness can be stressors of sleep disturbance ( 12 ). Superficially, sleep disturbance hinders elderly adults from performing daily roles such as taking care of children or driving.…”
Section: Introductionmentioning
confidence: 99%